Lightweight end-to-end blockchain for IoT applications - Lee, Seungcheol; Lee, Jaehyun; Hong, Sengphil; Kim, Jae Hoon (KSII Transactions on Internet and Information Systems, 2020)
Internet of Things (IoT) networks composed of a large number of sensors and actuators generate a huge volume of data and control commands, which should be enforced by strong data reliability. The end-to-end data reliability of IoT networks is an essential industrial enabler. Blockchain technology can provide strong data reliability and integrity within IoT networks. We designed a lightweight end-to-end blockchain network that applies to common IoT applications. Its enhanced modular architecture and lightweight consensus mechanism guarantee its practical applicability for general IoT applications. In addition, the proposed blockchain network is highly software compatible because it adopts the Hyperledger development environment. Directly embedding the proposed blockchain middleware platform in small computing devices proves its practicability.
Keywords: Computing devices; Data reliability; Development environment; Internet of Things (IOT); IOT applications; Middleware platforms; Modular architectures; Sensors and actuators; Hyperledger; Internet of Things; IoT; Lightweight blockchain